Seroprevalence, infection, and personal protective equipment use among Colombian healthcare workers during the COVID-19 pandemic - Beltrán, Edgar O.; Martignon, Stefania; Coronel-Ruiz, Carolina; Velandia-Romero, Myriam L.; Romero-Sanchez, Consuelo; Avila, Viviana; Castellanos, Jaime E. (Frontiers in Public Health, 2023)
Introduction: Healthcare workers (HCW) are at the first frontline of response to COVID-19 and are frequently exposed to the close contact with patients and virus contaminated body fluids. Recent studies have identified differential risk of infection and use of Personal Protective Equipment (PPE) among HCWs, however available data might be interpreted with caution because of the presence of differences in the health national systems, local implementation issues and adherence limitations to guidelines. A comprehensive description of infection, exposure at work and biosafety habits during the SARS-CoV-2/COVID-19 pandemic has not been conducted among HCWs groups in Latin-American populations. Objective: To describe SARS-CoV-2 seroprevalence, infections, and extent of PPE use during the COVID-19 pandemic at three different times, in HCWs, including dental practitioners (DP), nursing assistants (NA), physicians (P), and respiratory therapists (RT), from Bogotá, Colombia. Methods: After IRB approval, this cross-sectional study included 307 HCWs. Participants provided nasopharyngeal swabs and blood samples to detect viral RNA (RT-qPCR) and IgM/IgG anti-SARS-CoV-2 (ELFA-ELISA) in baseline (BL) and two follow-ups. Infection prevalence was defined as the number of tested positive participants (RT-qPCR and/or IgM). Clinical status and biosafety habits data were collected in each time. Results: Differential infection prevalence was found among HCWs through the study timeline (BL: RT-qPCR= 2.6%, IgM= 1.6%; follow-up 1 (45 days after BL): RT-qPCR= 4.5%, IgM= 3.9%; follow-up 2 (60 days after BL): RT-qPCR= 3.58%, IgM= 1.3%. Dental practitioners showed higher infection frequency in BL and follow-up 1. IgG positive tested HCWs percentage progressively increased from BL to the follow-ups among the whole sample while index values decreased. Limitations in N95 availability and high perception of occupational risk were reported. Conclusion: Low prevalence of active SARS-CoV-2 infection by occupation was found, This is a provisional file, not the final typeset article with increasing participants' IgG seroconversion and decreasing index values of these antibodies in serum. Moreover, restrictions in the use of PPE, and differential features in habits were reported by the HCWs.